The Utilisation of Zeolite To Eliminate The Price and Cost of Cement - Ahmad Nurfiki Alwi; Arif Rahman Setiaji; Abdurrohim Kurnia Agung; Abdul Halim (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2018)
The efficient cost of economic needs is the fundamental aspects to support the survival of an individual. Generally, the cost of the building in the residential community still utilise costly building materials and the installation costs are relatively expensive. Then, the technology of the bricks has been shifted to be the lightweight bricks. The lightweight bricks have better strength, lighter, faster installation and environmentally friendlier. Even though the lightweight bricks has many advantages, such as faster installation, the price of lightweight brick is still expensive. Therefore, to overcome the costly problem,  this research proposes the using of zeolites to replace the cement to reduce the production cost of bricks which also causes the elimination of lightweight brick price. This paper used the experiment method which evaluated by two way ANOVA to test the comparison of Zeolite composition with Fly Ash and Ca (OH) 2. In this case, we utilised zeolites containing silica by using the composition of 20%, 40% and 60%. Before using Zeolite, we activated Fly Ash with the composition of the ratio by 65% Fly Ash and 35% Zeolite; also 50% Fly Ash and 50% Zeolite. In 65% Zeolite, we employes 35% Ca (OH), and the 50% Zeolite contains 50% Ca (OH). Thus, there are 15 compositions including the control composition. Each composition yields 10 specimens.